2018
DOI: 10.1177/1541931218621112
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning from one Electronic Health Record (EHR) to Another: A Narrative Literature Review

Abstract: This paper reports the results of a literature review of health care organizations that have transitioned from one electronic health record (EHR) to another. Ten different EHR to EHR transitions are documented in the academic literature. In eight of the 10 transitions, the health care organization transitioned to Epic, a commercial EHR which is dominating the market for large and medium hospitals and health care systems. The focus of the articles reviewed falls into two main categories: (1) data migration from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…18 Although automated conversion can migrate structured data reliably, underlying discrepant structures and embedded content can cause data inconsistencies and compromise patient safety. 1,28 One incident highlighted a technology error in which data conversion caused a patient's medication dosage to be double the intended dose. 25 A formal risk assessment with near-real time supervisory review processes should be effected prior to automated data migration.…”
Section: Data Migrationmentioning
confidence: 99%
See 3 more Smart Citations
“…18 Although automated conversion can migrate structured data reliably, underlying discrepant structures and embedded content can cause data inconsistencies and compromise patient safety. 1,28 One incident highlighted a technology error in which data conversion caused a patient's medication dosage to be double the intended dose. 25 A formal risk assessment with near-real time supervisory review processes should be effected prior to automated data migration.…”
Section: Data Migrationmentioning
confidence: 99%
“…Clinicians report they appreciate additional staff for training and support. 28 One challenge is the "retreat of the army of a dedicated team after the initial go-live phase." 8 Practitioners believed the availability of ongoing training for more than 6 months can greatly reduce user frustration.…”
Section: Training and Supportmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, workflow disruptions or distractions such as provider training may negatively impact quality of care in the phase immediately before or after such a transition. Along these lines, there are conflicting single site reports of patient safety issues following EHR implementations and transitions [10][11][12][13][14] . While a recent study found no increase in patient safety events following EHR transitions in a cohort of adult hospitals 15 , there is limited evidence beyond dated, single site studies in pediatric hospitals, which carry their own set of unique operational health technology challenges.…”
Section: Introductionmentioning
confidence: 99%